To the question of card systemrationing of food distribution and industrial products in the central Ukraine at the final stages of World war II. - Galchenko S. І. (Вісник Черкаського університету. Серія: Історичні науки, 2016)
In the article the author reveals solutions how to provide the urban population through the organization of card system in the final stages of World War II. The cardbureaua ctivities and problems are characterized, which encountered during the last. Separately stated submission to Narodnyi Commissariat. Also the attention was paid to the problem of printing forms of these vital documents that were made at a special patterned paper and supplying them to the cardbureaus. Typically, the card issued to a predefined lists for job or address and documents were of strict accountability. Most cards have a specific design with clearly specified rules. The author drew attention to the problem of the existence in the lists of the so-called "DeadSouls", which was proved by the public authorities and involved punishment for perpetrators up to imprisonment from 2 to 5 years. Analyzing the normalized supply system the author noticed very important fact that no money cards do not used and therefore the level of foodstuff in each family depended on the number of employees and dependents were in it. The size of the salaries, pensions , allowances or scholarships (for students and trade schools) significantly affect the level of provision and consumption. Also, who had the misfortune to lose monthly cards were threatened to hungry or half-starved existence because no card reviewed. Once per month there was re- cards of the workers to withdraw from the account of those who resigned. People of working age who are not held a job were given cards only for bread, with fat and meat supply them removed .